Pengenalan Pembukuan Sederhana untuk Entrepreneur Masa Depan di SMK Putra Pertiwi, Tangerang Selatan - Aditya Riky Nugroho; Haryoso, Gunung Subagyo Anom; Ibram P. Dalimunthe (Universitas Pamulang, 2025)
This community service aims to provide knowledge and insights about the preparation of Financial Statements and taxation for MSMEs. The service was conducted at SMK Putra Pertiwi in South Tangerang. The target of this service is the students of SMK Putra Pertiwi in South Tangerang. The issues faced by the partners were addressed through several stages of activities, namely preparation, implementation, and evaluation. Preparation was carried out by conducting preliminary surveys related to the problems faced by the partners. Implementation was done through training and mentoring using a presentation method, followed by discussions and Q&A sessions. The evaluation of this stage was conducted by collecting and summarizing data from each stage of the activities. The results of the community service activities show a level of success with the alignment of the topic material with the information needed by the students to face future challenges. The students of the vocational school after completing their studies will be in the community and have the opportunity to develop themselves in the field of entrepreneurship at the micro, small, and medium enterprises (MSMEs) level. This service has encouraged participants to respond to the community service materials and to increase their knowledge and awareness about the importance of simple bookkeeping for MSME actors as well as the application of taxes. Keywords: financial report; taxation; socialization